ANALISA KEHIDUPAN SARA: PRIBADI DAN SPIRITUAL - Milton T. Pardosi (Fakultas Filsafat Universitas Advent Indonesia, 2019)
Sarai (or Sara) is the wife of Abram (or Abraham). She is the first fourwomen named in the Bible. There are many interesting things that could beresearched and taken from Sara’s life including her personal life; as a wife; as amother; and as a believer in Yahweh. The purpose of this paper was to find out theinteresting things of the life of Sara that need to be imitated, especially by women inmodern times. This is deemed necessary because Sarah is exemplified as an exampleof faith in Hebrews 11 and her faith is aligned with the faith of Abraham, herhusband. The results of this paper are: (1) Sara was a beautiful woman, an attractiveperson despite having a personal struggle; (2) Sarah was a wife who deeply loved herhusband, faithful, firm but submissive to the husband even willingly in honey for thehappiness of her husband and the integrity of the household; (3) Sara was a goodmother and loved Isaac that is why Isaac loved her so much. She was ready tosacrifice just for the happiness of her child; (4) Sarah was a woman who has a firmfaith in Yahweh. She was aligned as the figures of faith in the book of Hebrews. Shebelieved in God’s promises even though she had never enjoyed the land of Canaan;she never saw the great Israelites and the coming of Messiah. The positivecharacters of Sarah need to be copied by women in modern times if they want tomaintain their self-credibility; the integrity of their household; the future of theirchildren; especially their faith in Yahweh.